PERAN UNICEF DALAM MENANGANI KORBAN GEMPA DI NEPAL TAHUN 2015 - Nur Indah Mayang Sari; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explain about the role of UNICEF in dealing with victims of the earthquake in Nepal 2015. The research also describes how the impact of the earthquake in Nepal and how the condition of Nepal after the earthquake. The earthquakes in April and May 2015 took the lives of nearly 9,000 people. The earthquakes injured thousands and turned to rubble a huge number of homes, health posts and schools that faced the brunt of the quakes. UNICEF as one of the world institutions that fight for children's rights, has made many changes, working with communities and influencing governments in Nepal.This research theoretically has built with pluralism perspective on International Relations and supported by group behavior analysis, international organization theories, and also the concept of the role.The techniques used to collects data to study the case to library research in the form of journals, books, official document, article, and website. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is about UNICEF’s role to dealing with victims of the earthquake in Nepal.UNICEF started its response to the disaster right from day one on 25 April 2015. UNICEF launched an emergency appeal to cover the needs of the immediate response and early recovery phase. By using resources contributed towards this emergency appeal, UNICEF supported a number of life-saving activities across the areas of health; nutrition; water, sanitation and hygiene(WASH); education; child protection; and social protection. In addition, UNICEF engaged in helping to disseminate messages to assist children and their families stay safe and healthy during the disaster, as well as information on relief efforts in their communities.Keyword: earthquake, role, UNICEF, Nepal